Keragaman Kumbang (Coleoptera: Famili Tenebrionidae) di Distrik Bonggo, Kabupaten Sarmi, Papua - Evie L. Warikar (Jurusan Biologi FMIPA Universitas Cenderawasih, 2012)
Diversity study of beetles from Family of Tenebrionidae was conducted at forest areas in the district Bonggo, Sarmi Papua from September-October 2010. The Beetles were collected using a cross-wet trap placed at three locations in the former logged merbau (Intsia sp.) and sengon (Albisia sp.) areas. The data collected were the number of species and number of individuals in each species with indicators to compare beetle diversity based on species richness (s). The result showed that out of a total of 8 individuals of Tenebrionidae, there were seven different species identified during field observations. The highest number of beetles was found in the former logged Intsia spare as (4 species at third location and 2 species at the first location) followed by former logged Albisia sp areas (1 species at both locations).Key words: diversity, beetles, Tenebrionidae; Bonggo District, Jayapura.